Analisis Ukuran Efek Pengaruh Penggunaan Bahan Ajar Terhadap Kemampuan Berfikir Kreatif Siswa - Naurah Nazifah; Asrizal Asrizal; Festiyed Festiyed (Jurnal Pijar Mipa, 2021)
Industrial revolution 4.0 requires students to have 21st century skills. 21st century skills, is everyone who master the 4C which is the means to achieve success in people's lives in this 21st century. one of the 4Cs is creative thinking skills. The 2013 curriculum actually accommodates 21st century skills and demands that students be able to compete with the wider community. a teacher must prepare the teaching materials needed in the learning process before learning activities are carried out in order to achieve learning objectives. The research method used is a review article. There are 20 national and international journal articles This study aims to determine the effect of teaching materials on students 'creative thinking skills in terms of education level, subject matter, types of teaching materials, and students' creative thinking skills. From the data analysis conducted, four research results can be stated, namely: the use of effective teaching materials for students' creative thinking skills.